Expression and subcellular distribution of native estrogen receptor β in murine C2C12 cells and skeletal muscle tissue - Milanesi, Lorena Magdalena (2009)
We have recently described the expression and intracellular localization of ER α in murine C2C12 cells and skeletal muscle tissue. In separate studies, a protective role of 17β-estradiol against apoptosis exerted mainly at the mitochondrial level was also shown in the C2C12 muscle cell line. However, this functional evidence was in accordance with the participation of ER β. We have then here investigated the expression and subcellular distribution of native ER β in similar skeletal muscle cultured cells and tissue developed in vivo. ER β was detected by immunoblotting using specific antibodies and ligand blot analysis after subcellular fractionation. Immunolocalization was confirmed using conventional and confocal microscopy. ER β was found to a great extent in mitochondria and in lower amounts in the cytosolic fraction, differently to ER α which localizes in microsomes, cytosol, mitochondria, and also in the nucleus of muscle tissue. ER β expression was also demonstrated by RT-PCR. Finally, the mitochondrial localization of native ER β in C2C12 muscle cells was corroborated after transient transfection with specific ER β siRNAs. These data raise the possibility that the antiapoptotic action of 17β-estradiol in muscle cells may be related in part to a direct action of the hormone on mitochondria through ER β.